2014
DOI: 10.5603/cj.a2013.0089
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation practice patterns among cardiac electrophysiologists and cardiologists

Abstract: (Cardiol J 2014; 21, 3: 293-298)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…In the Euro Heart Survey on AF, the prevalence of flecainide or propafenone use for paroxysmal and persistent AF among all rate and rhythm control drugs was only 17% and 13%, respectively [ 19 ]. This is comparable to recent data reported in the United States where only electrophysiologists were found to prescribe these drugs [ 20 ]. The use of Class Ic antiarrhythmics had greatly decreased after the publication of the Cardiac Arrhythmia Suppression Trial (CAST) in 1991 [ 21 ], which showed increased mortality when these drugs were used for suppression of premature ventricular beats in ischemic heart disease.…”
Section: Discussionsupporting
confidence: 89%
“…In the Euro Heart Survey on AF, the prevalence of flecainide or propafenone use for paroxysmal and persistent AF among all rate and rhythm control drugs was only 17% and 13%, respectively [ 19 ]. This is comparable to recent data reported in the United States where only electrophysiologists were found to prescribe these drugs [ 20 ]. The use of Class Ic antiarrhythmics had greatly decreased after the publication of the Cardiac Arrhythmia Suppression Trial (CAST) in 1991 [ 21 ], which showed increased mortality when these drugs were used for suppression of premature ventricular beats in ischemic heart disease.…”
Section: Discussionsupporting
confidence: 89%
“…Available evidence suggests that rate control may be an appropriate strategy in older patients with minor symptoms, while rhythm-control may be used in patients who are symptomatic despite adequate rate control. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that rate control may be an appropriate strategy in older patients with minor symptoms, while rhythm-control may be used in patients who are symptomatic despite adequate rate control. 18 Based on the available data at the time, 80 bpm was chosen as the definition of adequate rate control in our study protocol, and this was chosen to allow comparison with the global RECORD AF study. The results of the RACE (Rate Control Efficacy in Permanent Atrial Fibrillation) II trial, which showed lenient (,110 bpm) control to be noninferior to strict (,80 bpm) control, 19 have resulted in the suggestion that lenient rate control may be a reasonable strategy in patients with permanent AF and stable ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…Dofetilide, a class III antiarrhythmic drug, is approved for the treatment of persistent atrial fibrillation (AF) . Although proven efficacious, dofetilide continues to be underused for treatment of persistent AF when compared with other antiarrhythmic drugs . This is largely due to prolongation of corrected QT interval (QTc) and concerns for associated life‐threatening ventricular arrhythmias…”
Section: Introductionmentioning
confidence: 99%